2017
DOI: 10.1016/j.nmni.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

First case of Nocardia amamiensis pulmonary infection in Mexico

Abstract: We report a case of Nocardia amamiensis pulmonary infection in a 43-year-old immunocompromised woman. The patient was treated with imipenem/cilastatin and trimethoprim/sulfamethoxazole and had a favourable outcome. It is important that laboratories perform species identification to understand the epidemiology and susceptibility patterns of the different Nocardia spp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…N. amamiensis , identified as a novel species, was first isolated from a sugarcane field in Japan in 1997 by Yamamura H. et al [ 8 ]. However, only six cases of nocardiosis caused by N. amamiensis have been reported to date, with detailed descriptions available for just three of those cases [ 9 , 10 , 13 ]. Furthermore, previous reports or studies on the epidemiology of nocardiosis have rarely included cases caused by N. amamiensis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…N. amamiensis , identified as a novel species, was first isolated from a sugarcane field in Japan in 1997 by Yamamura H. et al [ 8 ]. However, only six cases of nocardiosis caused by N. amamiensis have been reported to date, with detailed descriptions available for just three of those cases [ 9 , 10 , 13 ]. Furthermore, previous reports or studies on the epidemiology of nocardiosis have rarely included cases caused by N. amamiensis .…”
Section: Discussionmentioning
confidence: 99%
“…It appears that patients with underlying diseases or those undergoing treatment with immunosuppressive agents are more susceptible to N. amamiensis pulmonary infection. The first report of pulmonary infection caused by N. amamiensis was published by Martinez-Gamboa A. et al, in 2016 [ 10 ]. The current case represents only the fourth reported case and is the first to be reported in an immunocompetent patient without structural pulmonary disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bhagyanarayanae and N. amamiensis were the most frequent species found on Sichang Island. Infection caused by N. amamiensis is rare, with only two ocular and two pulmonary infections previously reported [26,27]. In 2016, Martinez-Gamboa et al reported pulmonary infection caused by N. amamiensis in Mexico.…”
Section: Antimicrobial Susceptibility Of Nocardia Isolatesmentioning
confidence: 99%
“…In 2016, Martinez-Gamboa et al reported pulmonary infection caused by N. amamiensis in Mexico. The strain was susceptible to trimethoprim-sulfamethoxazole, amoxicillin/clavulanic acid, imipenem, and amikacin [27]. Reddy et al reported two strains of N. amamiensis isolated from ocular infection [26].…”
Section: Antimicrobial Susceptibility Of Nocardia Isolatesmentioning
confidence: 99%